Kebijakan Media Interaktif: Belum Melancarkan Sistem Komunikasi Indonesia - Ana Nadhya Abrar (FISIP Universitas Atma Jaya Yogyakarta, 2008)
Abstract: Some people believe that the communication policy determines the communication system. However, communication policy should be made to create good communication system. It means that to make the communication policy, people should considering the prior communication system. Relating to the interactive media policy, as a kind of communication policy, made by the Indonesian government, this article is intended to explore the relation between that policy and the Indonesian communication system. This article offers the thesis that the interactive media policy has been made by the government without fully considering to the communication system. It is indicated by: (1) not seriously considering the nature of interactive media, (2)not seriously enforcing people to make the social changes, and (3) not responsive.